UDK 656.052 METHODS OF DETERMINING TRANSPORT FLOWS - Rasulmuhamedov, Muxamadaziz; Tashmetov, Komoliddin; Tashmetov, Timur (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The study of traffic flow and its effective management holds paramount significance in contemporary urban infrastructure. Accurate methods for assessing traffic patterns are crucial for enhancing road safety, optimizing transportation systems, and alleviating traffic congestion. This article delves into the various methodologies and technologies employed for traffic detection and control. From inductive sensors to advanced computer vision systems, these techniques offer diverse strategies for monitoring and analyzing traffic.